Makna Komunikasi Nonverbal Upacara Adat Momasoro di Desa Ogoansam, Kecamatan Palasa, Kabupaten Parigi Moutong - Hanifa (Kinesik, 2024)
Momasoro is a boat release, a ritual of the Lauje tribe that is carried out at the end of each year as a form of gratitude to the Creator who provides fertility for the crops and life for plants and animals. Momasoro is a means of treatment that is believed by the Lauje tribe. The results of the study indicate that the meaning of the nonverbal message contained in the Momasoro traditional ceremony procession of the Lauje Tribe is based on several aspects. Kinesics are seen from the movements and facial expressions of officers in the Momasoro traditional ceremony procession during the process of circling the boat while mogumbuy and when dancing Meaju to deliver the boat on the beach. Paralinguistics are seen from the mongganoy process (reading prayers using rhythm) accompanied by sinta, gong and dotolan musical instruments performed by one of the traditional elders in Ogoansam Village. Artifacts are seen from the equipment that has been provided by the traditional elders and the Lauje Tribe community in Palasa District.